Qualidade de frutos de tomate ‘giuliana’ tratados com produtos de efeitos fisiológicos - Pereira Ramos, Anamaria Ribeiro [UNESP]; Esteves Amaro, Amanda Cristina [UNESP]; Macedo, Ana Claudia [UNESP]; Assis Sugawara, Guilherme Shigueyuki de [UNESP]; Evangelista, Regina Marta [UNESP]; Rodrigues, João Domingos [UNESP]; Ono, Elizabeth Orika [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The present work evaluated the effect of strobilurins, boscalid, plant growth regulators and vegetal extracts on the physico-chemical quality of tomato fruits (Solanum lycopersicum L.), hybrid Giuliana. The fruits from each treatment were selected and separated in 4 repetitions: control, pyraclostrobin, boscalid, pyraclostrobin + boscalid, IBA + GA(3) + kinetin, GA(4+7) + benzylaminopurine and vegetal extract. The first application was carried out at 30 days after transplant and the following at every 15 days. The evaluations were: weight loss, titratable acidity (TA), soluble solids (SS), SS/TA relation, pH, ascorbic acid content, texture, total soluble sugars (TSS), activity of pectin methyl esterase (PME) and polygalacturonase (PG). The SS content, responsible for fruit flavor, varied accordingly to the treatment, being highest for GA(4+7) + benzylaminopurine and lowest for the control. The same occurred regarding the SS/AT relation. The fruits were kept on the shelf for 9 days, at room temperature, being that at the end of this period several treatments still presented fruit in optimal consumption conditions, notably the boscalid treatment, which presented lowest weight loss, followed by pyraclostrobin. Therefore, it can be concluded that the application of the treatments did not modify the values for pH, AT and AST of the fruits. The highest PME activity was observed for the treatments with boscalid and the mixture of boscalid and pyraclostrobin, while the lowest PG activity occurred in the control and the pyraclostrobin treatment, indicating that some products accelerated the process of demethylation of pectins by PME, facilitating the action of PG.
Fruit quality of tomato 'giuliana' treated with products with physiological effects
Keywords: Solanum lycopersicum; strobilurins; boscalid; plant growth regulators; postharvest; plant extract